18F-fluorodeoxyglucose positron emission tomography/computed tomography as a metabolic marker for functional assessment of spinal tuberculosis after early decompression surgery - Rangan, Kasturi; Israrahmed, Amrin; Suraj, Ajay; Gambhir, Sanjay (World Journal of Nuclear Medicine, 2021)
Tuberculosis (TB) of the spine is the most important extra pulmonary form of TB. The lytic destructive variant of spinal TB can destroy the intervertebral discs, vertebral body, collapse, kyphotic deformity, and spinal cord compression. Complicated Pott's disease if not managed early can lead to neurological deficits, so there is a need for early surgical decompression, compliant anti-tubercular therapy, and response evaluation tool. We present two cases of multilevel dorsal spinal TB diagnosed on magnetic resonance imaging spine and baseline 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) scan. They underwent early decompression with internal fixation and were followed up for 18 months with serial 18F-FDG PET/CT at 3rd and 18th month, respectively. One patient showed an early complete metabolic response and excellent functional recovery. Another patient showed progressive disease (drug-resistant status) and delayed functional recovery. 18F-FDG PET/CT has an excellent role in assessing response to therapy and thus helps to achieve therapeutic endpoint.
Keywords: 18F-fluorodeoxyglucose positron emission tomography; computed tomography in spinal decompression assessment; 18F-fluorodeoxyglucose positron emission tomography; computed tomography in spinal tuberculosis; monitoring pott's spine